Study and design of wide band low noise amplifier operating at C band - Hoi, Tran Van; Duong, Bach Gia (VNU Journal of Science: Mathematics - Physics; Vol 29 No 2, 2013)
Abstract : This paper reports on design and fabrication of wide band low noise amplifier (LNA) atC band, which is used for satellite receiver systems. The most important thing in the design of the LNA is to compromise importance characteristics such as gain, noise figure, stability, bandwidth. The results of this paper introduce an approach to design the LNA with gain as high as possible, bandwidth 800 MHz and the lowest noise figure. All the designed, simulated and fabricated processes were done using Agilent’ ADS 2009 package. The LNA has successfully been fabricated using microtrip technology and pHEMT transistor amplifier with following specifications: Maximum overall gain is 23.9 dB, operating frequency from 3.4 GHz to 4.2 GHz, standing wave ratio is less than 1.9, the reverse isolation: -41dB, input and output impedance: 50 Ω.  Keywords: LNA, C band, noise figure, satellite receiver, ADS .